Frequency of Systems ABO and Rh in People Who Went to the Welfare Academic Service of Clinical Analyses - Quispe A., Peter (2008)
ABO and Rhesus blood group system were determined from 3655 patients attending The Assitentíal Service of Clinical Ana1ysis bclonging to Facultad de Farmacia y Bioquímica of Universidad Nacional Mayor de San Marcos in the period of time betwccn 2003 and 2005, the goal of this study was to estímate the frequency of blood group system ABO and Rh in the population under study and to compare our findings with other investigations. It was used specific anti serum; moreover, all test were conducted following conventional methodology. The statistic analysis of results provided the following frequencies: 73.36%0+, 0.38%0-, 18.85%A+, 0.27 A-, 5.85%B+ and 1.45%AB%+. The differences of frequencies of ABO and Rh blood system were related to the Peruvian geographic region to which patients carne from. Also, it was found slight differences when thc results obtained from this investigation were compared with previous studies.